Econometric Mediation Analyses: Identifying the Sources of Treatment Effects from Experimentally Estimated Production Technologies with Unmeasured and Mismeasured Inputs - James J. Heckman; Rodrigo Pinto (Institute for the Study of Labor (IZA), 2013)
This paper presents an econometric mediation analysis. It considers identification of production functions and the sources of output effects (treatment effects) from experimental interventions when some inputs are mismeasured and others are entirely omitted.
Keywords: C21; C38; C43; D24; 330; production function; mediation analysis; measurement error; missing inputs; Produktionsfunktion; Ökonometrie; Test